2020
DOI: 10.1186/s12879-020-04997-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of isoniazid preventive therapy completion among people living with HIV attending care and treatment clinics from 2013 to 2017 in Dar es Salaam Region, Tanzania. A cross-sectional analytical study

Abstract: Background Tuberculosis (TB) disease is a common opportunistic infection among people living with HIV (PLHIV). WHO recommends at least 6 months of isoniazid Preventive Therapy (IPT) to reduce the risk of active TB. It is important to monitor the six-month IPT completion since a suboptimal dose may not protect PLHIV from TB infection. This study determined the six-month IPT completion and factors associated with six-month IPT completion among PLHIV aged 15 years or more in Dar es Salaam region, Tanzania. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
3
8
1
Order By: Relevance
“…In this case, the transfer-in facility may not offer care continuity (in this case INH) due to a lack of relevant documentation from the transfer-out facility (64). This finding is similar to a study done in Dar es salaam where people living with HIV who were transferred to other clinics within Dar es Salaam region after IPT initiation had significantly lower IPT completion levels compared to those that attended the same clinic (57). These findings are also similar to studies conducted in Zimbabwe and Ethiopia (26, 65).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this case, the transfer-in facility may not offer care continuity (in this case INH) due to a lack of relevant documentation from the transfer-out facility (64). This finding is similar to a study done in Dar es salaam where people living with HIV who were transferred to other clinics within Dar es Salaam region after IPT initiation had significantly lower IPT completion levels compared to those that attended the same clinic (57). These findings are also similar to studies conducted in Zimbabwe and Ethiopia (26, 65).…”
Section: Discussionsupporting
confidence: 89%
“…Distance to the health facility was cited as one of the barriers to IPT completion as patients could not afford transport every month to the health facility to pick up their IPT doses. This echoes findings from studies conducted in Tanzania, Zimbabwe, and Ethiopia which found that patients were discouraged by the need to attend clinic every month combined with the long treatment duration of IPT (26, 56, 57). A significant proportion of patients do not get ART from their nearest facility (58, 59) due to various reasons that include the fear of stigma, and the perception that care at local facilities being of lower quality compared to distant ones (59, 60).…”
Section: Discussionsupporting
confidence: 47%
“…Similar barriers identified in this study have been identified in TPT evaluations completed in other countries in Africa, including the lack of services and medication availability, provider concern about promoting drug resistance, lack of clarity about appropriate candidates, and viewing TPT as a low priority among competing healthcare needs. Additionally, recent analyses in South Africa/Uganda, Zimbabwe and Tanzania described TPT cascade completion rates between 15 and 49%, similar to what was observed in in Namibia [36][37][38].…”
Section: Discussionsupporting
confidence: 72%
“…We observed that patients not on ART or newly initiated on ART were associated with low IPT completion before 2019 compared to their ART experienced counterparts. Similarly, some previous studies found that TPT completion was associated with being on ART (7,29). Patients who are new or not on ART are likely to have stigma (30,31), poor adherence (32), and lack of understanding of the role of TB prevention in the absence of symptoms (33).…”
Section: Acknowledgmentsmentioning
confidence: 81%